Analysis of The Dominant Factors Affecting Premenstrual Syndrome (PMS) in Female Students of The Pesantren Darussalam Purwokerto - Awaliyatun Istiqomah; Siti Haniyah; Tin Utami (LPPM Universitas Harapan Bangsa, 2024)
The transition from childhood to adulthood known as puberty is a transformative phase marked by the growth of reproductive organs, which impacts physical and mental evolution, and changes in social roles. One of the major physiological changes in the reproductive organs during this period is the onset of menstruation. At the time of menstruation until menstruation begins, women generally experience several symptoms. This is called premenstrual syndrome, which occurs cyclically 7-10 days before menstruation and disappears 4 days after menstruation. The main cause behind PMS is hormonal instability, especially the disharmony between estrogen and progesterone, and variations in serotonin levels. The purpose of this study was to determine the dominant factors that influence Premenstrual syndrome (PMS) in female students at the Darussalam Islamic Boarding School in Purwokerto. This type of research is quantitative research using a descriptive research method with a cross-sectional research design, because this research was conducted by means of an approach, observation or data collection at one time. The research sample involved a group of 76 female adolescents aged 15 to 18 years. Various questionnaires were used for data collection, such as SPAF, PSS, GPA, and PSQI. Logistic regression test was used for data analysis. The results showed a significant p value of 0.001 < 0.05, indicating a relationship between. The results showed that students with poor sleep quality had a 9 times higher risk of developing PMS than students with good sleep quality, even after considering factors such as stress levels and physical activity (p value = 0.001; OR = 9.110; 95% CI = 2.601-31.913).